Respuesta :

Answer:

-23

Step-by-step explanation:

x = -5 lies in the last piece

h(-5) = 4(-5) - 3

= -20 - 3

= -23

Step-by-step explanation:

Step 1:  Find which piece-wise function it is in

Equation 1 → x < -7

Let x = -5 → (-5) < -7 ← False

Equation 2 → -7 ≤ x < -5

Let x = -5 → -7 ≤ (-5) < -5 ← False

Equation 3 → x ≥ -5

Let x = -5 → (-5) ≥ -5 ← True

Step 2:  Find the value of h(-5)

[tex]h(-5) = 4x - 3[/tex]

[tex]h(-5) = 4(-5) - 3[/tex]

[tex]h(-5) = -20 - 3[/tex]

[tex]h(-5) = -23[/tex]

Answer:  [tex]h(-5) = -23[/tex]

ACCESS MORE